Let's solve the system of equations using the elimination method step by step.
Given equations:
\[
\begin{cases}
8x + 7y = 39 \quad \text{(1)} \
4x - 14y = -68 \quad \text{(2)}
\end{cases}
\]
Step 1: Multiply the First Equation
To eliminate the \(y\)-term, we can multiply the first equation (1) by \(2\) so that the coefficients of \(y\) in both equations will match in magnitude (since \(7\) in equation (1) becomes \(14\) after multiplication):
\[
2(8x + 7y) = 2(39) \
16x + 14y = 78 \quad \text{(new equation 1)}
\]
Step 2: Write the System of Equations
Now we have the modified system of equations:
\[
\begin{cases}
16x + 14y = 78 \quad \text{(new equation 1)} \
4x - 14y = -68 \quad \text{(2)}
\end{cases}
\]
Step 3: Add the Equations to Eliminate the \(y\)-terms
Now add the two equations together to eliminate the \(y\)-terms:
\[
(16x + 14y) + (4x - 14y) = 78 + (-68)
\]
This simplifies to:
\[
16x + 4x + 14y - 14y = 78 - 68
\]
\[
20x = 10
\]
Step 4: Solve the New Equation for \(x\)
Now solve for \(x\):
\[
x = \frac{10}{20} = \frac{1}{2}
\]
Step 5: Substitute the \(x\)-value into Either Original Equation
Now substitute \(x = \frac{1}{2}\) back into one of the original equations to find \(y\). Let's use equation (1):
\[
8\left(\frac{1}{2}\right) + 7y = 39
\]
This simplifies to:
\[
4 + 7y = 39
\]
Subtract \(4\) from both sides:
\[
7y = 39 - 4
\]
\[
7y = 35
\]
Now divide by \(7\):
\[
y = 5
\]
Step 6: Check the Solution
To check, substitute \(x = \frac{1}{2}\) and \(y = 5\) into both original equations.
For equation (1):
\[
8\left(\frac{1}{2}\right) + 7(5) = 39 \
4 + 35 = 39 \quad \text{(True)}
\]
For equation (2):
\[
4\left(\frac{1}{2}\right) - 14(5) = -68 \
2 - 70 = -68 \quad \text{(True)}
\]
Both equations hold true with the given values.
Final Answer
The solution to the system of equations is:
\[
\left(\frac{1}{2}, 5\right)
\]
Thus, the final answer is \((\frac{1}{2}, 5)\).